Comparison of Femoral Head Rotation and Varus Collapse Between a Single Lag Screw and Integrated Dual Screw Intertrochanteric Hip Fracture Fixation Device Using a Cadaveric Hemi-Pelvis Biomechanical Model. Issue 4 (April 2016) - Santoni, Brandon G.; Nayak, Aniruddh N.; Cooper, Seth A.; Smithson, Ian R.; Cox, Jacob L.; Marberry, Scott T.; Sanders, Roy W.
Abstract : Objective: This study compared the stabilizing effect of 2 intertrochanteric (IT) fracture fixation devices in a cadaveric hemi-pelvis biomechanical model. Methods: Eleven pairs of cadaveric osteopenic female hemi-pelves with intact hip joint and capsular ligaments were used. An unstable IT fracture (OTA 31-A2) was created in each specimen and stabilized with a single lag screw device (Gamma 3) or an integrated dual screw (IDS) device (InterTAN). The hemi-pelves were inverted, coupled to a biaxial apparatus and subjected to 13.5 k cycles of loading (3 months) using controlled, oscillating pelvic rotation (0–90 degrees) plus cyclic axial femoral loading at a 2:1 body weight (BW) ratio. Femoral head rotation and varus collapse were monitored optoelectonically. For specimens surviving 3 months of loading, additional loading was performed in 0.25 × BW/250 cycle increments to a maximum of 4 × BW or failure. Results: Femoral head rotation with IDS fixation was significantly less than the single lag screw construct after 3 months of simulated loading ( P = 0.016). Maximum femoral head rotation at the end of 4 × BW loading was 7× less for the IDS construct ( P = 0.006). Varus collapse was significantly less with the IDS construct over the entire loading cycle ( P = 0.021). Conclusions: In this worst-case model of an osteopenic, unstable, IT fracture, the IDS construct, likely owing to its larger surface area, noncylindrical profile, and fracture compression, provided significantly greater stability and resistance to femoral head rotation and varus collapse. Abstract : Supplemental Digital Content is Available in the Text.